PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA BOOKLET TERHADAP TINGKAT KECEMASAN PADA PENDERITA HIPERTENSI DI PUSKESMAS OEPOI-WILAYAH KERJA KOTA KUPANG - Ariyance Hana Ndapaole (CHMK NURSING SCIENTIFIC JOURNAL, 2020)
Background: Hypertension is a serious problem and always causes anxiety because of someone's ignorance of hypertension such as causes, complications and methods of prevention or treatment. Due to these conditions, is expected to provide health education about hypertension regularly so that patients can control themselves from the disease, to reduce the level of anxiety they felt. According to the World Health Organization (WHO) in 2014 there were one billion people in the world suffering from hypertension. Two thirds of them found in developing countries with low to moderate income, such as Indonesia. The purpose of this study was to determine the effect of health education by using booklet media towards the level of anxiety in hypertensive patients at Oepoi Community Health Center in the Work Area of Kupang City.This research used pre-experimental method with one-group pre-post test design. The sampling technique used was purposive sampling with 30 sample respondents. The results showed a decrease in anxiety levels in hypertensive patients after getting health education by using booklet media. The results of the research hypothesis test used Wilcoxon statistical test and obtained a value of p = 0,000. The data is said to have an effect if p <0.05 so that H1 is accepted, which means there was a significant influence on the provision of hypertension with booklet media towards anxiety levels in hypertensive patients at Oepoi Health Center - the Work Area of Kupang City. Suggestion: It is expected that the results of this study can be used as input for the implementation of health education which has been running in Oepoi Health Center so that it is maintained and carried out periodically health education related to Non-Communicable Diseases (NCD) in this case one of which is hypertension. Keywords: Anxiety, Booklet, Health Education, Hypertension